Financial globalisation and financial development in Africa: assessing marginal, threshold and net effects - Simplice A. Asongu; Lieven De Moor (African Governance and Development Institute (AGDI), 2015)
The present inquiry contributes to extant literature by simultaneously accounting for variations in financial development and financial globalisation in the assessment of hypothetical initial financial development conditions for the rewards of financial globalisation. The policy relevance for assessing these variations simultaneously builds on the intuition that, thresholds for financial development benefits of financial globalisation may also be contingent on initial levels of financial development. For this purpose, we examine marginal, threshold and net effects of financial globalisation on financial development throughout the conditional distributions of financial development. The empirical evidence is based on contemporary and non-contemporary quantile regressions with data from 53 African countries for the period 1996-2011. Financial globalisation is measured with Net Foreign Direct Investment inflows whereas financial development entails all dimensions identified by the Financial Development and Structure Database of the World Bank. The findings consistently reveal: (i) positive marginal effects, (ii) unfeasible financial globalisation positive thresholds and (iii) negative financial globalisation net effects. The second and third findings are fundamentally due to marginal effects of low positive magnitude. Policy implications are discussed.
Keywords: F02; F21; F30; F40; O10; 330; Banking; International investment; Financial integration; Development